The narrative approach in teaching the tafsir course and its effectiveness in developing conceptual comprehension for third year middle school students - Alsanawi, Abdullah Fahad (Journal of Curriculum and Teaching Methodology, 2023)
The aim of the research is to identify the effectiveness of the narrative approach in teaching the interpretation course in developing the conceptual comprehension of the third intermediate grade students. The conceptual understanding that was built according to the list of conceptual comprehension skills prepared by the researcher; The research resulted in a number of results, the most important of which are: the presence of a statistically significant difference at the level of significance (α ≤ 0.05) between the mean scores of the students of the experimental group and the scores of the control group in the conceptual comprehension test in favor of the experimental group, and the presence of a statistically significant difference at the level of significance (α ≤ 0.05) among the mean scores of the experimental group students between the pre and post applications in the conceptual comprehension test in favor of the post application; In light of the results of the research, the researcher made a number of recommendations related to these results, including: Emphasizing the use of the narrative approach in building and teaching legal science courses in general and the interpretation course in particular.